Effectiveness of hyaluronic acid in the treatment of degenerative diseases of the temporomandibular joint: Literature Review - Diego Fernandez-Vial; Fernando Silva-Arce; Nicole Renner (Universidad de Concepción., 2021)
Objetive:The degenerative diseases of the tempo-romandibular joint (TMJ) are characterized by a progressive destruction of the articular tissues of the condyle and the glenoid fossa. The main aim of this review is to describe the effectiveness of the hyaluronic acid (HA) in the treatment of degenerative diseases of the TMJ in accordance with the available scientific evidence. Material and Methods: A literature search was made in the following databases EBSCO, Pubmed, Cochrane and Trip Database, using the keywords hyaluronic, hyaluronan, NaH, hyaluronate, TMJ, TMD, CMD, craniomandibular, orofacial pain and temporomandibular. There were no date or language restrictions applied. Results: After applying inclusion and exclusion criteria, 14 studies were included in this review (11 randomized controlled clinical trials and 3 non-randomized clinical trials). Conclusion: The studies reported a decrease in pain and improvement in functional parameters after treatment of TMJ osteoarthritis with HA. The use of arthrocentesis associated with the administration of HA provides effects synergistic, reaching a superiority the protocols with multiple injections with respect to those of a single session. The adverse effects related to the injection of HA with or without associated arthrocentesis were minor and transitory.